THE QUALITY OF BAKTERIOLOGIS STUDY AND USE OF WATER OR DUG WELLS WITH AN OCCURRENCE WATER BORNE DISEASES IN THE VILLAGE WEST PASAYANGAN - Agustina, Norsita; Hayati, Ridha; Irianty, Hilda (Preventif: Jurnal Kesehatan Masyarakat, 2018)
Background & Objective : Clean water which could cause bakteriologis water quality ineligible .This study attempts to know the quality of water bakteriologis a well (the bacteria MPN coliformm and e.coli ) consumed villagers west Pasayangan Kabupaten Banjar in the water borne disease and relations the behavior of the people in the water borne disease. Materials and method: This research methods used the cross sectional. The study analyzed by the quality of bakteriologis (MPN coliform and E. Coli ) as many as 30 a well. Data obtained through observation, interview using a questionnaire and results laboratory.Results bakteriologis water quality a well suggests that the whole water a well ineligible clean water developed by the minister of health no. 416 / menkes / per / ix / 1990. Result: The results showed that source of drinking water and management of drinking water had links scene water borne disease. Conclusion: The quality of bakteriologis well water dig they did not qualified drinking water and there was a correlation between the clean and healthy living (PHBS) in a household with a water borne diseases .Was recommended to the community to need to do and healthy patterns of living water management well with the way of chlorine in and cook water with the right way before use